2013
DOI: 10.1021/es304455k
|View full text |Cite
|
Sign up to set email alerts
|

PCBs and OH-PCBs in Serum from Children and Mothers in Urban and Rural U.S. Communities

Abstract: East Chicago, Indiana is a heavily-industrialized community bisected by the Indiana Harbor and Ship Canal, which volatilizes ~7.5 kg/yr polychlorinated biphenyls (PCBs). In contrast, the rural Columbus Junction, Iowa area has no known current or past PCB industrial sources. Blood from children and their mothers from these communities were collected April 2008-January 2009 (n=177). Sera were analyzed for all 209 PCBs and 4 hydroxylated PCBs (OH-PCBs). Sum PCBs ranged from non-detect to 658 ng/g lw (median = 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
199
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(231 citation statements)
references
References 46 publications
14
199
6
1
Order By: Relevance
“…Here, we evaluated and supported the predictions of a RyR-based neurotoxic QSAR that has been used to define NEQs for NDL PCBs (Rayne and Forest, 2010). As predicted, PCB 202 is a highly RyR potent PCB congener, and whereas it is detected in human and environmental samples, it likely does not represent a large percentage of total PCB burdens (Marek et al, 2013;Stahl et al, 2009). However, similar to TCDD in the TEQ scheme, PCB 202 could act as a reference compound for which PCB mixture toxicity toward the RyR is based.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Here, we evaluated and supported the predictions of a RyR-based neurotoxic QSAR that has been used to define NEQs for NDL PCBs (Rayne and Forest, 2010). As predicted, PCB 202 is a highly RyR potent PCB congener, and whereas it is detected in human and environmental samples, it likely does not represent a large percentage of total PCB burdens (Marek et al, 2013;Stahl et al, 2009). However, similar to TCDD in the TEQ scheme, PCB 202 could act as a reference compound for which PCB mixture toxicity toward the RyR is based.…”
Section: Resultsmentioning
confidence: 94%
“…Deficits in children have included lowered IQ scores, impaired learning and memory, and attention deficit (Jacobson and Jacobson, 1996;Lonky et al, 1996;Stewart et al, 2008). It is well recognized that PCB residues in these samples are complex mixtures but neurotoxic outcomes due to PCB mixture exposure have been largely ascribed to NDL congeners because they are found in relatively high concentrations in the brains of human and experimental animals that display neuropsychological deficits (Mitchell et al, 2012;Pessah et al, 2010) NDL PCBs also constitute the majority of the total PCB burden in both human and environmental samples (Hwang et al, 2001(Hwang et al, , 2006Marek et al, 2013;Stahl et al, 2009) and further understanding the contribution of the RyR, alone or in combination with other modes of NDL PCB neurotoxicity (see "Introduction" section), would help further elucidate risks in human populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be due to higher exposure levels from the urban surroundings. In a study from the USA, where urban and rural communities also were compared, a difference in concentration level was not found, but the presence of PCBs in the serum samples was significantly more frequent in the urban samples [44]. In our study, PCB 28 was the only PCB congener that showed higher rural than urban concentrations, which is notable, because it indicates that children living in the rural area are exposed to higher levels of volatized PCBs, perhaps from school or living buildings.…”
Section: Ahr-teq In Mothers and Childrenmentioning
confidence: 90%
“…Despite their ubiquity throughout the planet, environmental concentrations in a particular region are conditioned by the past use of these chemical compounds in it. So it has been reported that in urban areas and in the most industrialized regions the levels of contamination by PCBs of the population are much higher than in rural areas (Ampleman et al, 2015;Marek et al, 2013). In this sense, Spain and Morocco are completely different, and therefore it is expected that the levels of contamination by these chemicals are also different.…”
Section: Introductionmentioning
confidence: 99%